The Role of Cadaver-Based Flap Course in Microsurgical Education and Practice Patterns of Attendees: A Survey Study - Azoury, Saïd C.; Othman, Sammy; Colen, David L.; Broach, Robyn B.; Lin, Ines; Zenn, Michael R.; Kovach, Stephen J.; Levin, L. Scott (Journal of Reconstructive Microsurgery, 2020)
Background In 2017, our institution initiated a cadaver laboratory-based course dedicated to teaching reconstructive microsurgery indications, preoperative planning, and flap dissection. The goals of this study are to describe the demographics and experience of participants/instructors and to evaluate the learning objectives and effectiveness of the course.Methods Penn Flap Course (PFC) participants were sent an anonymous survey at the inaugural PFC 2017. Then, in 2019, both instructors and participants were sent a more comprehensive survey. Surveys included questions regarding demographics, training background, experiences in practice and/or training, and course evaluation.Results At PFC 2017, participant response rate was 25% (12/44), and the primary reason for attending the course was to observe and learn from instructor dissections (66.7%). At PFC 2019, the response rate was 77.3% (17/22) for faculty and 73.0% (35/48) for participants. Both in 2017 and 2019, the vast majority of participants reported perceived improvement in understanding of flap dissection principles across all anatomic domains (94.3%–100%). In 2019, when asked about their background experience, the majority of participants reported comfort performing arterial and venous anastomosis without supervision (71%–77%) and being least comfortable with head and neck (H&N) microsurgery (mean comfort level: 5.2/10). Half of the participants (e.g., residents) find the presence of a microsurgery fellow at their institution useful to their educational experience. Instructors with additional fellowship training in microsurgery reported performing a higher volume of free flaps per week (7 vs. 2.3) and per year (94.2 vs. 27.8; p < 0.05 for both) and trend toward performing more H&N reconstruction (p = 0.057).Conclusion Participants feel least comfortable with H&N microsurgical reconstruction. Surgical faculty with microsurgical fellowship training performs greater volume of microsurgical cases with a trend toward more H&N reconstruction. A cadaver/lecture-based flap course is an effective way to improve participants' perceived confidence and understanding of complex flap and microsurgical reconstructive procedures.
Keywords: education; cadaver; flap course